Variable mating behaviors and the maintenance of tropical biodiversity - Cannon, Charles H.; Lerdau, Manuel (Frontiers in Genetics, 2015)
Current theoretical studies on mechanisms promoting species co-existence in diverse communities assume that species are fixed in their mating behavior. Each species is a discrete evolutionary unit, even though most empirical evidence indicates that inter-specific gene flow occurs in plant and animal groups. Here, in a data-driven meta-community model of species co-existence, we allow mating behavior to respond to local species composition and abundance. While individuals primarily out-cross, species maintain a diminished capacity for selfing and hybridization. Mate choice is treated as a variable behavior, which responds to intrinsic traits determining mate choice and the density and availability of sympatric inter-fertile individuals. When mate choice is strongly limited, even low survivorship of selfed offspring can prevent extinction of rare species. With increasing mate choice, low hybridization success rates maintain community level diversity for extended periods of time. In high diversity tropical tree communities, competition among sympatric congeneric species is negligible, because direct spatial proximity with close relatives is infrequent. Therefore, the genomic donorship presents little cost. By incorporating variable mating behavior into evolutionary models of diversification, we also discuss how participation in a syngameon may be selectively advantageous. We view this behavior as a genomic mutualism, where maintenance of genomic structure and diminished inter-fertility, allows each species in the syngameon to benefit from a greater effective population size during episodes of selective disadvantage. Rare species would play a particularly important role in these syngameons as they are more likely to produce heterospecific crosses and transgressive phenotypes. We propose that inter-specific gene flow can play a critical role by allowing genomic mutualists to avoid extinction and gain local adaptations.